New asymptomatic thrombosis caused by carotid web during the acute period of cerebral infarction - Yan Wang; Hai-Lei Li; Xiao-Hua Xu; Jin-Hao Ye; Jian Li (BMC Neurology, 2023)
Abstract Background At present, the carotid web (CaW) as an important cause of cryptogenic ischemic stroke has gradually received clinical attention. CaW is associated with a high risk of stroke and patient is more likely to have recurrent stroke if the CaW is untreated. We report a patient who developed CaW related thrombosis during the acute period of cerebral infarction. Case presentation A 49-year-old male patient with CaW in the left internal carotid artery was diagnosed by computed tomography angiography (CTA) and had two cerebral infarctions in two years. Within 72 h after thrombolysis for an acute cerebral infarction, acute thrombosis was identified between the web and the posterior wall of the carotid artery on carotid ultrasound. Emergent carotid endarterectomy (CEA) was performed to remove abnormal CaW structures and thrombosis to prevent stroke. The patient recovered well and was asymptomatic at 2 months follow-up. Conclusion Carotid web related thromboembolism is a rare cause of stroke. Carotid ultrasound plays an important role in the diagnosis of asymptomatic thrombosis caused by carotid web. Carotid endarterectomy is effective for stroke prevention in patient with carotid web related thrombosis.